You have the equation y = 5x and an x value, x = 13.

1. Substitute the x value into your equation.

y = 5(13)

2. Simplify by performing the multiplication.

y = 65

Since you already know that x = 13, you can simply plug 13 in for x in the original equation.

Therefore, put 13 in place of x in y = 5x.

5 multiplied by 13 is 65.

So, y = 65.

To find the value of y at point x=13, we need to substitue x for its value in the equation. In other words, replace x with 13 in your problem.

`y=5x=>y=5*13=65`